The Relationship between Source Credibility and Political Participation: Examining the Egyptian Talk Show “Masr Al Yom” broadcast on Al Faraeen Satellite Channel - Abdel Raouf, Riham Ibrahim (AUC Knowledge Fountain, 2014)
This study set out to assess the credibility of Egyptian talk show host Tawfik Okasha and how it affects the political participation tendencies of his viewers. The results showed that he was highly rated on the components of expertness and trustworthiness and moderately on the component of goodwill. Overall, Tawfik Okasha was perceived as a credible communicator. Tawfik Okasha’s credibility varied among the different educational levels. He is mostly credible among the “illiterate” and the “less than high school” categories. Compared to the rest of the educational levels, highly educated people do not perceive Tawfik Okasha as credible. Perceiving Tawfik Okasha as credible was found to be associated with active political participation among the respondents. The results also showed that respondents who perceive Okasha as credible are more likely to vote for the candidates he supports. Okasha’s use of nationalist discourse has been shown to enhance his credibility.